Activation of eNOS by D-pinitol Induces an Endothelium-Dependent Vasodilatation in Mouse Mesenteric Artery - Luciana N. Moreira; Josiane F. Silva; Grazielle C. Silva; Virgínia S. Lemos; Steyner F. Cortes (Frontiers Media S.A., 2018)
D-pinitol is a cyclitol present in several edible plant species and extensively investigated for the treatment of metabolic diseases in humans, as food supplement, and demonstrated protective effects in the cardiovascular system. For these reasons, the present work aimed at investigating the mechanisms involved in the vascular effects of D-pinitol in mouse mesenteric artery. Mesenteric arteries from male C57BL/6 mice were mounted in a wire myograph. Nitrite was measured by the 2,3-diaminonaphthalene (DAN) method. Protein expression and phosphorylation were measured by Western blot. The systolic blood pressure (SBP) was measured by tail-cuff plethysmography. D-pinitol induced a concentration-dependent vasodilatation in endothelium-intact, but not in endothelium-denuded arteries. Nω-Nitro-L-arginine methyl ester (300 μM) abolished the effect of D-pinitol, while 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ; 10 μM) shifted the concentration-response curve to the right. KN-93 (1 μM) blunted the vasodilator effect of D-pinitol, but H-89 (0.1 μM) did not change it. 1-[2-(Trifluoromethyl) phenyl]imidazole (300 μM), indomethacin (10 μM), celecoxib (5 μM), wortmannin (1 μM), ruthenium red (10 μM), tiron (10 μM), MnTMPyP (30 μM), MPP (0.1 μM), PHTPP (0.1 μM), and atropine (1 μM) did not change the effect of D-pinitol. D-pinitol increased the concentration of nitrite, which was inhibited by L-NAME and calmidazolium (10 μM). D-pinitol increased the phosphorylation level of eNOS activation site at Ser1177 and reduced the phosphorylation level of its inactivation site at Thr495. In normotensive mice, the intraperitoneal administration of D-pinitol (10 mg/kg) induced a significant reduction of the SBP after 30 min. The present results led us to conclude that D-pinitol has an endothelium- and NO-dependent vasodilator effect in mouse mesenteric artery through a mechanism dependent on the activation of eNOS by the calcium-calmodulin complex, which can explain its hypotensive effect in mice.